Comparative Analysis and EST Mining Reveals High Degree of Conservation among Five Brassicaceae Species. (20th September 2010) - Bhati, Jyotika; Sonah, Humira; Jhang, Tripta; Singh, Nagender Kumar; Sharma, Tilak Raj
Abstract : Brassicaceae is an important family of the plant kingdom which includes several plants of major economic importance. The Brassica spp. and Arabidopsis share much-conserved colinearity between their genomes which can be exploited for the genomic research in Brassicaceae crops. In this study, 131, 286 ESTs of five Brassicaceae species were assembled into unigene contigs and compared with Arabidopsis gene indices. Almost all the unigenes of Brassicaceae species showed high similarities with Arabidopsis genes except those of B. napus, where 90% of unigenes were found similar. A total of 9, 699 SSRs were identified in the unigenes. PCR primers were designed based on this information and amplified across species for validation. Functional annotation of unigenes showed that the majority of the genes are present in metabolism and energy functional classes. It is expected that comparative genome analysis between Arabidopsis and related crop species will expedite research in the more complex Brassica genomes. This would be helpful for genomics as well as evolutionary studies, and DNA markers developed can be used for mapping, tagging, and cloning of important genes in Brassicaceae .